Virtual screening for inhibitors of the human TSLP:TSLPR interaction. Issue 1 (December 2017) - Van Rompaey, Dries; Verstraete, Kenneth; Peelman, Frank; Savvides, Savvas; Augustyns, Koen; Van Der Veken, Pieter; De Winter, Hans
Abstract The pro-inflammatory cytokine thymic stromal lymphopoietin (TSLP) plays a pivotal role in the pathophysiology of various allergy disorders that are mediated by type 2 helper T cell (Th2) responses, such as asthma and atopic dermatitis. TSLP forms a ternary complex with the TSLP receptor (TSLPR) and the interleukin-7-receptor subunit alpha (IL-7Rα), thereby activating a signaling cascade that culminates in the release of pro-inflammatory mediators. In this study, we conducted anin silico characterization of the TSLP:TSLPR complex to investigate the drugability of this complex. Two commercially available fragment libraries were screened computationally for possible inhibitors and a selection of fragments was subsequently testedin vitro . The screening setup consisted of two orthogonal assays measuring TSLP binding to TSLPR: a BLI-based assay and a biochemical assay based on a TSLP:alkaline phosphatase fusion protein. Four fragments pertaining to diverse chemical classes were identified to reduce TSLP:TSLPR complex formation to less than 75% in millimolar concentrations. We have used unbiased molecular dynamics simulations to develop a Markov state model that characterized the binding pathway of the most interesting compound. This work provides a proof-of-principle for use of fragments in the inhibition of TSLP:TSLPR complexation.